Analisis Kesalahan Siswa SMK PGRI 4 Blitar dalam Menyelesaikan Soal pada Materi Trigonometri - Saputra, Riko Aditya; Nisa, Sitta Khoirin; Pramesti, Cicik; Suryanti (Polinomial : Jurnal Pendidikan Matematika, 2025)
Mathematical errors refer to students’ inaccuracies in understanding, applying, or communicating mathematical concepts and procedures, which lead to answers that deviate from the expected results. Therefore, this study aims to analyze the types of errors made by Grade X students at SMK PGRI 4 Blitar in solving trigonometry problems, specifically on the topics of special angles, the sine rule, the cosine rule, and the area of a triangle. This research employs a qualitative descriptive method involving three students selected based on their levels of mathematical ability: high, medium, and low. Data were collected through written tests and interviews, and were analyzed using three categories of errors: conceptual, procedural, and communicative. The findings indicate that students made various types of errors—including conceptual, procedural, and communicative—committed by participants SP1, SP2, and SP3. These errors stemmed from a lack of understanding of basic concepts, incorrect problem-solving procedures, and difficulties in communicating mathematical ideas, including the representation and notation of mathematical symbols during the learning process. This study provides a clear picture of the challenges students face in understanding trigonometry and offers valuable insights for evaluating and improving mathematics teaching strategies at the vocational high school level.